Myasthenia Gravis and Myeloproliferative Neoplasms – Mere Association or Paraneoplastic Neurologic Syndrome: A Mini-Review - Sasi, Sreethish; Mohamed, Mouhand; Chitrambika , P; Yassin, Mohamed (Acta Biomedica Atenei Parmensis, 2022)
Myasthenia Gravis (MG) is a rare neurological condition characterized by muscle weakness that worsens after use. Myeloproliferative Neoplasms (MPNs) are disorders due to stem-cell hyperplasia characterized by an increased peripheral blood cell count, overactive bone marrow, and proliferation of mature hematopoietic cells. MPNs may be Philadelphia (Ph) chromosome-positive or Negative .A systematic review of case reports was conducted by searching PubMed, Scopus, and Google scholar to identify case reports in which there is an association between MG and MPN and know whether MG can be considered a possible neurological paraneoplastic syndrome in patients with MPNs. A total of 13 cases of MPNs associated with MG were identified. The most common type of MPN associated with MG was chronic myeloid leukemia (CML) (10 out of 13 patients).  In most of the patients, MG symptoms appeared after a diagnosis of MPN was made. Considering that 10 out of the 13 patients in our cohort had positive auto-antibodies though only 4 of them had thymic hyperplasia, we hypothesize that bone marrow proliferation was responsible for the production of autoantibodies in these patients.As the clonal cell population cannot be eliminated entirely in the bone marrow even after treatment with tyrosine kinase inhibitors (TKI) in Ph +ve MPNs and JAK2 inhibitors in Ph -ve MPNS, MG can occur even in patients who are treated with these agents. A high index of suspicion is needed to diagnose it early, and treatment should be initiated immediately with steroids and anticholinergic agents.